The molecular world cup: Synthesis of a fullerene-calix[4]arene conjugate containing two malonamide substituents within the upper rim - Soi, Antonio; Hirsch, Andreas (New Journal of Chemistry, 1998)
A molecular counterpart of the football world cup was synthesized by twofold cyclopropanation of C with a calix[4]arene containing two malonamide substituents within the upper rim.